Accuracy evaluation method for multi-tasking turning centre. (26th July 2011) - Muditha Dassanayake, K.M.; Cui, Chengri; Tsutsumi, Masaomi
Multi-tasking turning centre has ten inherent deviations which were identified by considering the axis configuration and mutual motions of axes. To estimate all these deviations, in this paper, a new methodology which is based on simultaneous three-axis motion technique is proposed. The effects of deviations on predefined trajectories were investigated by simulations. Five measurements which were extracted by conducting four simultaneous motions were used in the identification algorithm. All the ten inherent deviations were estimated accurately by means of the centre offset values of the trajectory measurement. Furthermore, the effects of setting errors of balls of ball bar and clamp-unclamp process of B-axis on measurement were discussed and eliminating techniques were proposed. All the results were verified by means of simulations and experiments. Based on the results, it can be said that the proposed method can be used as an accuracy evaluation and identification tool for multi-tasking turning centres.